Giulia Bogliolo Bruna, Jean Malaurie, une énergie créatrice, Paris, Armand Colin, 2012, pp. 339 - Luisa Faldini (Anuac, 2015)
Book review of Giulia Bogliolo Bruna, Jean Malaurie, une énergie créatrice, Paris, Armand Colin, 2012, pp. 339.